THE HOUSEHOLD ADAPTATION TOWARD ENVIRONMENTAL CONDITION CAUSED BY TOFU INDUSTRY: CASE STUDY OF GG. FAMILY, SATELITTE AND SURYA IN SINGKAWANG, INDONESIA - , WAN FARDIYANSYAH ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This study has assessed the impact between the perception of people and the environment, what causes it and the way they respond to the pollution in the case of tofu industry which is very polluting industry because of liquid waste and bad odour. This research was focused on Gg. Family, Satelit and Surya in Singkawang city, West Kalimantan, Indonesia where there were 8 tofu industries. The stratified random sampling was used to understand the factors that influence householdsâ perception related to gender. The total numbers of respondents were 100 households divided into two categories which were 50 men and 50 women by questioner and interviewed 8 respondents to explore in-depth information. The type of this research was a descriptive-case study. The research result found that the most important things that influence perception are education, ethnicity, age, attitude, motive, interest, expectation, occupation, income, closed family and proximity. The different levels of education, age and ethnicity influence attitude, motive, interest, expectation, occupation and income of people to the environmental perception. The research result also found that there was a very low awareness of the pollution particularly among lower education of Chinese and older people that are a big group in this community. Based on adaptation, respondents did adaptation as an individual by closing the nose using a hand and closing doors and windows when they smelled bad odor. However, some respondents did nothing. The respondents also renovated their house and joined the community service of physical and social adaptation. Awareness campaign is needed to improve the environmental awareness particularly focusing on the Chinese community, the older people that lower educated people and the people who have bad or not think much of the environmental pollution. The group of people that seem very aware, the higher educated people and people who are the member of community organization can be used to create awareness in the community. Rules and better waste management system would have to improve the perception of people.